Urban Metabolism, interdisciplinary models and design at micro-urban scale - Pollo, Riccardo; Trane, Matteo; Giovanardi, Matteo (TECHNE - Journal of Technology for Architecture and Environment, 2021)
The architecture and the micro-urban scale design are elected to disciplines capable of materializing society’s perennial and rapid evolution demands. The design quality derives from its characteristic of opening up to external contamination, making work on the frontiers of knowledge and the hybridization of knowledge crucial. The contribution reflects on the Urban Metabolism’s (UM) role as a boundary metaphor, within which interaction among the scientific community, stakeholders, policymakers, and designers is possible. This metaphor could then be understood as a potential investigation and design tool for the Urban Ecosystem. UM’s possible relationship with architecture and environmental design is investigated, starting from models and approaches typical of other disciplinary fields.